Developing a New Recipe for Milk Chocolate - Hovhannisyan, N. G.; Manukyan, A. H. (ՀԱԱՀ հիմնադրամ)
The aim of the current research is to produce new chocolate products with some amount of vitamin content. At the same time, a more cost-effective raw material has been used as a leguminous mass, namely apricot kernel, which usually serves as a secondary raw material in the juice production. The technology of functional milk chocolate production has been developed based on the sprouted apricot kernel, which is a source for B1, B2 vitamins. The developed technology can be easily introduced in the production and will promote the development of national chocolate industry.
Keywords: Food Science and Technology